Important Role of Mitochondrial Dysfunction in Immune Triggering and Inflammatory Response in Rheumatoid Arthritis - Li P; Zhou M; Wang J; Tian J; Zhang L; Wei Y; Yang F; Xu Y; Wang G (Journal of Inflammation Research)
Pingshun Li,1,2 Mengru Zhou,2 Jia Wang,2 Jiexiang Tian,2 Lihuan Zhang,2 Yong Wei,2 Fang Yang,2 Yali Xu,1 Gang Wang2 1College of Integrative Chinese and Western Medicine, Gansu University of Chinese Medicine, Lanzhou, 730000, People’s Republic of China; 2Department of Rheumatology and Bone Disease, Affiliated Hospital of Gansu University of Chinese Medicine, Lanzhou, 730000, People’s Republic of ChinaCorrespondence: Gang Wang, Email 2645433166@qq.comAbstract: Rheumatoid arthritis (RA) is an inflammatory autoimmune disease, primarily characterized by chronic symmetric synovial inflammation and erosive bone destruction.Mitochondria, the primary site of cellular energy production, play a crucial role in energy metabolism and possess homeostatic regulation capabilities. Mitochondrial function influences the differentiation, activation, and survival of both immune and non-immune cells involved in RA pathogenesis. If the organism experiences hypoxia, genetic predisposition, and oxidative stress, it leads to mitochondrial dysfunction, which further affects immune cell energy metabolism, synovial cell proliferation, apoptosis, and inflammatory signaling, causing the onset and progression of RA; and, mitochondrial regulation is becoming increasingly important in the treatment of RA.In this review, we examine the structure and function of mitochondria, analyze the potential causes of mitochondrial dysfunction in RA, and focus on the mechanisms by which mitochondrial dysfunction triggers chronic inflammation and immune disorders in RA. We also explore the effects of mitochondrial dysfunction on RA immune cells and osteoblasts, emphasizing its key role in the immune response and inflammatory processes in RA. Furthermore, we discuss potential biological processes that regulate mitochondrial homeostasis, which are of great importance for the prevention and treatment of RA.Keywords: mitochondria, rheumatoid arthritis, immune triggers, inflammatory response, osteoblasts, synovial cells